Relative dose intensity over the first four weeks of lenvatinib therapy is a factor of favorable response and overall survival in patients with unresectable hepatocellular carcinoma - Sakura Kirino; Kaoru Tsuchiya; Masayuki Kurosaki; Shun Kaneko; Kento Inada; Koji Yamashita; Leona Osawa; Yuka Hayakawa; Shuhei Sekiguchi; Mao Okada; Wan Wang; Mayu Higuchi; et al. (2020)
Lenvatinib is an approved first-line therapy for unresectable hepatocellular carcinoma (HCC), but the effect of dose modification on its efficacy is unclear. We analyzed the relationship between the relative dose intensity during the initial 4 weeks of therapy [4W-relative dose intensity (RDI)] and the efficacy of lenvatinib therapy in the real-world setting. A total of 48 consecutive patients with unresectable HCC who received lenvatinib therapy for more than 4 weeks were included. The 4W-RDI was calculated as the cumulative dose in the initial 4 weeks divided by the weight-based standard dose, and we evaluated its association with overall survival (OS) and best response by modified Response Evaluation Criteria in Solid Tumor (mRECIST). The baseline factors predicting high 4W-RDI were analyzed further. The median durations of follow-up and of therapy among the 48 participants were 7.6 and 6.6 months, respectively. The median OS was not reached. Drug interruption and/or dose reduction were necessary in 30 patients (62.5%) and the median 4W-RDI was 70% (range 22%-100%). Patients with 4W-RDI ≥70% had longer OS [hazard ratio (HR) 0.28, 95% confidential interval (CI):0.09-0.90, p = 0.03], and longer duration of lenvatinib therapy (HR 0.39, 95%CI:0.16-0.92, p = 0.03). Patients with 4W-RDI ≥70% showed higher disease control rate compared to those with 4W-RDI <70% (91.7% vs. 54.2%, p = 0.008). A baseline albumin level >3.4g/dL or ALBI score less than -2.171 were significantly associated with achieving 4W-RDI ≥70%. In conclusion, 4W-RDI of lenvatinib therapy is associated with favorable radiological response and longer OS.